Natural disaster handbook - Cobb, Regina (New York Syrawood publishing house, 2019)
Natural disasters are adverse events that are caused by natural processes of the Earth. These include earthquakes, volcanic eruptions, floods, tsunamis, tornadoes and hurricanes. Natural disasters can be classified into geological disasters, hydrological disasters, meteorological disasters, space disasters and wildfires. Geological disasters include avalanches and landslides, earthquakes and volcanic eruptions.
Keywords: Natural disasters; Weather; Cyclones